A Hybrid Approach of Preprocessing and Segmentation Techniques in Automatic Rice Variety Identification System - Komal; Sethi, G. K.; Bawa, R. K. (Journal of Scientific Research, 2022)
Image processing techniques play an important role with various images such as rice grain identification, wheat, fruits, medical, vehicle, and digital text images in image acquisition, image preprocessing, clustering, segmentation, and classification techniques. In the application of object detection and classification images, preprocessing and segmentation techniques are used. This paper delves into the specifics of automated segmentation processes, focusing on rice variety identification and classification images. The aim is to talk about the issues that come up when segmenting digital images and the relative merits and drawbacks of the various methods for preprocessing and segmenting images that are currently available. In this paper, we propose a hybrid approach of Preprocessing and Segmentation techniques to develop an automatic rice variety identification system.